2015
DOI: 10.1007/s10548-015-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Network Differences Between Migraineurs and Non-migraine Controls: fMRI Evidence

Abstract: Migraine is a headache disorder characterized by sensitivity to light and sound. Recent research has revealed abnormal visual-spatial attention in migraineurs in between headache attacks. Here, we ask whether these attentional abnormalities can be attributed to specific regions of the known attentional network to help characterize the abnormalities in migraine. Specifically, the ventral frontoparietal network of attention is involved with assessing the behavioural relevance of unattended stimuli. Given the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 43 publications
6
27
0
Order By: Relevance
“…There is no observable evidence that the attentional capture and arousal effects of the distracting sounds were different among migraineurs compared to control participants at the behavioral level. This result is in line with a previous study finding no increased impact over performance of visual distractors during a visual cueing task in migraine [40].…”
Section: Exacerbated Bottom-up Attentional Effects In Migrainesupporting
confidence: 94%
“…There is no observable evidence that the attentional capture and arousal effects of the distracting sounds were different among migraineurs compared to control participants at the behavioral level. This result is in line with a previous study finding no increased impact over performance of visual distractors during a visual cueing task in migraine [40].…”
Section: Exacerbated Bottom-up Attentional Effects In Migrainesupporting
confidence: 94%
“…42 Frontal regions that contributed to migraine subclassification in this study likely participate in affective and cognitive components of pain processing, and many are regions previously identified as aberrant in migraine. 43,44 Compared to individuals who have migraine without allodynia, those who have migraine with allodynia have been shown in prior studies to have aberrant paininduced activation of middle frontal gyrus and somatosensory cortex and altered functional connectivity with regions including the precuneus, middle and superior temporal gyri, middle and superior frontal gyri, and inferior and superor parietal gyri, all regions that contributed to migraine subclassification within this study. 25,27 Also, several regions that contributed to migraine subclassification in this study also contributed to migraine classification models consisting of brain structure or function in previously published studies (many of the research participants in those studies were also included in the current study).…”
Section: Discussionmentioning
confidence: 63%
“…Atypical function of these regions that integrate somatosensory, visual, and auditory stimuli might contribute to the hypersensitivies associated with migraine and the exacerbation of headache via visual and auditory stimuli . Frontal regions that contributed to migraine subclassification in this study likely participate in affective and cognitive components of pain processing, and many are regions previously identified as aberrant in migraine . Compared to individuals who have migraine without allodynia, those who have migraine with allodynia have been shown in prior studies to have aberrant pain‐induced activation of middle frontal gyrus and somatosensory cortex and altered functional connectivity with regions including the precuneus, middle and superior temporal gyri, middle and superior frontal gyri, and inferior and superor parietal gyri, all regions that contributed to migraine subclassification within this study .…”
Section: Discussionmentioning
confidence: 69%
“…Results of this study are intriguing and indicate a potential abnormal modulation of pain-cognition circuits in patients with migraine [70•]. Mickleborough et al (2015) [71] used an fMRI visual attention-orienting task to interrogate brain activation patterns in interictal migraineurs and healthy controls. Interestingly, although migraineurs performed as well as healthy controls on the attention task, migraineurs showed less activation of the ventral fronto-parietal attention network including the right temporal parietal junction, a region relevant for re-orienting attention to salient stimuli [71].…”
Section: Attention/cognition Deficits In Migraine: An Ongoing Debatementioning
confidence: 99%
“…Mickleborough et al (2015) [71] used an fMRI visual attention-orienting task to interrogate brain activation patterns in interictal migraineurs and healthy controls. Interestingly, although migraineurs performed as well as healthy controls on the attention task, migraineurs showed less activation of the ventral fronto-parietal attention network including the right temporal parietal junction, a region relevant for re-orienting attention to salient stimuli [71]. Results by Tessitore et al (2015) have indicated that, although migraineurs show weaker connectivity in their executive control network relative to healthy controls, there is an absence of performance deficits on a variety of neurocognitive measures [30].…”
Section: Attention/cognition Deficits In Migraine: An Ongoing Debatementioning
confidence: 99%